Mulla the key to Indian practice: a summary of the code of civil procedure - Mulla, Dinshaw Fardunji; Kannan, K (Gurgaon LexisNexis, 2019)
Widely acclaimed as a dussic, Mulla The Key to Indian Practice is a lucid and succinct exposition of the important provisions of the Code of Civil Procedure. Unraveling the complexities of the Code, it presents a systematic and precise account of the conduct of civil suits in Indian courts. The present edition preserves the original scheme as conceived and adapted by Sir Dinshow Fardunji Mulia, whilst incorporating latest developments in the subject
Keywords: Law; Code of Civil Procedure